2011
DOI: 10.1007/s13197-011-0425-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of omega-3 rich energy bar with flaxseed

Abstract: Energy bar sample were prepared with different levels of flaxseed (0-20%) in addition to cereals and pulses with varying levels of sweeteners (45, 50, and 55%) to deliver a nutritious food to the consumer. The developed bars were evaluated for textural, colour, nutritional quality, sensory attributes and total microbial load. Different levels of flaxseed and sweeteners significantly affected the hue and chroma values of the energy bar. In general the level of flaxseed in energy bar did not affect the hardness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 13 publications
9
35
0
1
Order By: Relevance
“…The protein content of different samples of energy bar was found in the range of 7.21-9.22% which was increased significantly with increasing level of potato extrudates but found decreased with increasing level of sweeteners due to dilution effect of honey and similar type of results were observed by Mridula et al (2013). Different levels of sweeteners statistically non significantly affect the ash content of different energy bar samples.…”
Section: Nutritional Composition Of Energy Barssupporting
confidence: 54%
See 1 more Smart Citation
“…The protein content of different samples of energy bar was found in the range of 7.21-9.22% which was increased significantly with increasing level of potato extrudates but found decreased with increasing level of sweeteners due to dilution effect of honey and similar type of results were observed by Mridula et al (2013). Different levels of sweeteners statistically non significantly affect the ash content of different energy bar samples.…”
Section: Nutritional Composition Of Energy Barssupporting
confidence: 54%
“…It was observed that, increasing levels of potato extrudates and sweeteners (specially honey) significantly increased moisture content of energy bar samples which was obvious (Mridula et al 2013) and this might be due to the higher water holding capacity of potato (Khaliduzzaman et al 2010). …”
Section: Nutritional Composition Of Energy Barsmentioning
confidence: 99%
“…Conversely, samples with lower sweetener exhibited crumbly texture while preparation and thus resulted in more hardness than samples with 55 % sweeteners. Similar findings have been reported by Mridula et al [9] in case of flaxseed-based energy bar. Further, the type of sweetener also affected the cutting strength significantly (P \ 0.001) ( Table 3) and highest value was observed for jaggery-based samples followed by honey-based and lowest for energy bar samples prepared using corn syrup as sweetener ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…The possible reason for increase in FFA content could be the breakdown of hydroperoxide [16]. Similar findings of FFA content increase with increasing storage period were reported in the omega-3 enriched flaxseed energy bar [9]. The relationship between the FFA content (F) and refrigerated storage (RS) period (in days) can be expressed by using the following regression equation:…”
Section: Instrumental Colour Qualitymentioning
confidence: 61%
“…The food products namely, flaxseed chutney [11], flaxseed chutney powder [12], peanut chikki incorporated with flaxseeds [13], flaxseed cookies [14], flaxseed energy bar [15], flaxseed soup mix [16], have been prepared owing to numerous health incentives and physiological wellness on flaxseed consumption.…”
Section: Introductionmentioning
confidence: 99%